PENGARUH LATIHAN FISIK (IN PATIENT) TERHADAP ACTIVITY OF DAILY LIVING PADA PASIEN DENGAN PENYAKIT JANTUNG SINDROM KORONER AKUTDI RSUD PROF. DR. W. Z. JOHANNES KUPANG - Kristina Tanggu Mala (CHMK Applied Science Journal, 2019)
Acute Coronary Syndrome (ACS) is called coronary arterial disease which is one of the most cardiovascular problems around the world. Thedisease causes high mortality rates in both developed and developing country including Indonesia. Patients who are suffering from ACS should have bed rest and activity limitation. The combination of patophisiology process of ACS and activity limitation would decrease the fungtional capacity of the patients’ and influence the self care ability and activity of daily living (ADL). Therefore, the ACS patients require inpatient physical exercise. The aim of the study:To evaluate the affect of physical exercixe (inpatient) to Acitivity of Daily Living of ACS patients in RGHProf. Dr. W. Z. Johannes Kupang. The method of the research is pre-experimental with one group pre-test – posttest design and the sampling technique is concecutive sampling which cultivated to 29 respondents. The statistical test that cultivated to test the research hypothesis is Wilcoxon Signed Rank Test. The result of the test showed that there was significant affect of physical exercixe (inpatient) to Acitivity of Daily Living of ACS patients in RGH Prof. Dr. W. Z. Johannes Kupang with p value = 0,000 which this value <α 0.05. Recommendation: the hospital could cultivatethe physical exercixe (inpatient) in the process of care for ACS patients. Kata Kunci : Physical Exercixe (inpatient), Activity of Daily Living, Acute Coronary Syndrome